Fully biobased epoxy resin systems composed of a vanillin-derived epoxy resin and renewable phenolic hardeners. (July 2017) - Shibata, Mitsuhiro; Ohkita, Tomoyuki
Graphical abstract: Highlights: A new biobased epoxy resin was synthesized from vanillin, cyclopentanone and epichlorohydrin. The biobased epoxy resin was cured with renewable phenolic hardeners to produce fully biobased materials. The glass transition temperatures were higher than those of petroleum-based products. The char yields at 500 °C were much higher than those of petroleum-based products. The flexural properties were comparable to those of petroleum-based products. Abstract: A new bio-based epoxy resin (DGEDVCP) was synthesized by the glycidylation of 2, 5-bis(4-hydroxy-3-methoxybenzylidene)cyclopentanone (DVCP) prepared by the crossed-aldol condensation of vanillin and cyclopentanone. The thermal and mechanical properties of DGEDVCP resins cured with renewable quercetin (QC) and guaiacol novolac (GCN) in addition to a petroleum-based phenol novolac (PN) were compared with those of bisphenol A diglycidyl ether (DGEBA) resins cured with QC, GCN and PN. Regarding the hardeners used for curing, the higher order of loss modulus ( E ″) peak temperature of cured products was QC > PN > GCN. The E ″ peak temperatures of DGEDVCP/GCN and DGEDVCP/PN cured products were higher than and comparable to those of DGEBA/GCN and DGEBA/PN cured products, respectively. Thermal degradation temperatures of DGEDVCP-based products were slightly lower than those of DGEBA-based products. Char yields at 500 °C for DGEDVCP-based products were much higher than those of DGEBA-based products. The flexural strengths and moduli of the DGEDVCP/QC and DGEDVCP/GCN cured products were comparable to those of DGEBA/QC and DGEBA/GCN cured products, respectively.